2013
DOI: 10.5296/jbls.v4i2.4091
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biochemically Improved Shrimp Industry Waste in Fry Tilapia (Oreochromis Niloticus, Linnaeus 1758) Diets: Effects on Growth Performance and Carcass Composition

Abstract: To evaluate the nutritional quality of the shrimp by-products four approximately isonitrogenous (32 ± 2% crude protein) diets containing different types of shrimp waste meal were fed to duplicate groups of ten fry with an initial mean weight 1.43 ± 0.22g /fish for forty two (42) days. Fishes fed with diet D had the highest mean weight gain (MWG) and specific growth rate (SGR) and those fed with the control diet A had the lowest MWG and SGR. ISSN 2157-6076 2013 www.macrothink.org/jbls 330 There were no noticea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
2
6
6
Order By: Relevance
“…Although shrimp meal is nutrient rich, several studies have shown that diet digestibility and fish growth are compromised when high proportions are used (Diop et al., ; Fall et al., ; Mugo‐Bundi et al., ; Synowiecki & Al‐Khateeb, ). Shrimp meals made from shrimp shells may contain relatively high amounts of indigestible fibres (chitin and chitosan), which build up when high proportions are used in diet (Fall et al., ; Synowiecki & Al‐Khateeb, ) and make nutrients less accessible by fish (Leal, Castro, Lima, Souza Correia, & Souza Bezerra, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although shrimp meal is nutrient rich, several studies have shown that diet digestibility and fish growth are compromised when high proportions are used (Diop et al., ; Fall et al., ; Mugo‐Bundi et al., ; Synowiecki & Al‐Khateeb, ). Shrimp meals made from shrimp shells may contain relatively high amounts of indigestible fibres (chitin and chitosan), which build up when high proportions are used in diet (Fall et al., ; Synowiecki & Al‐Khateeb, ) and make nutrients less accessible by fish (Leal, Castro, Lima, Souza Correia, & Souza Bezerra, ).…”
Section: Discussionmentioning
confidence: 99%
“…Shrimp meals made from shrimp shells may contain relatively high amounts of indigestible fibres (chitin and chitosan), which build up when high proportions are used in diet (Fall et al., ; Synowiecki & Al‐Khateeb, ) and make nutrients less accessible by fish (Leal, Castro, Lima, Souza Correia, & Souza Bezerra, ). Furthermore, the fibres interfere with emulsification, absorption and utilization of fats by fish (Deng et al., ; Diop et al., ). The chitin absorbs fats and bile in fish intestine (Tharanathan & Kittur, ) and reduces their availability for usage by fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fall et al (2012) reported that fish fed diet containing shrimp meal (SM) gained weight slightly less than those fed diet containing fishmeal. Diop et al (2013) revealed that the incorporation of shrimp by-products in the diets of tilapia at 45% gave the best weight gain (4.96 g) compared to the control diet. Several authors (Jung et al, 2006;Wenhong et al, 2008;Uno et al, 2010;Laila et al, 2010) have highlighted that there exist three methods of waste utilization from aquaculture or wild stocks, which are fishmeal, silage and organic fertilizer productions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been done on the inclusion of shrimp head meal in the fish feed formulation. Shrimp head meal in the fish diet increased daily growth rate (DGR), feed efficiency (FE), protein efficiency ratio (PER), survival and protein content of the fish (Fall et al, 2012;Diop et al, 2013). Moreover, Melati et al (2012) stated that shrimp head meal could be used to replace fishmeal protein up to 45% in the feed formulation for catfish in hatcheries.…”
Section: Introductionmentioning
confidence: 99%